2020
DOI: 10.1002/jmv.25873
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations in DNA‐repair genes (XRCC1, 3, and 7) and the susceptibility to hepatocellular carcinoma in a cohort of Egyptians

Abstract: Chronic hepatitis C (CHC) is a worldwide etiology of chronic hepatic insult particularly in Egypt. DNA‐repair systems are responsible for maintaining genomic integrity by countering threats posed by DNA lesions. Deficiency in the repair capacity due to genetic alterations in DNA‐repair genes can lead to genomic instability and increased risk of cancer development. The present work aimed at studying the possible association between XRCC1‐G28152A (rs25487), XRCC3‐C18067T (rs861539), and XRCC7‐G6721T (rs7003908) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…In a study performed among 50 HCC patients from the South Valley of Egypt, the authors revealed that the XRCC1 (rs25487*399Gln) allele was significantly increased with the progression of HCC ( p = 0.007) 47 . Likewise, in another study done among 100 HCC patients recruited from the Capital of Egypt, the authors identified that XRCC1 (rs25487*399Gln) allele revealed a statistically significant with an elevated risk of HCC ( p = 0.004) 13 . Furthermore, other reports confirmed the contribution of the XRCC1 (rs25487*p.Gln399Arg) variant with the elevated risk of HCC like those among Italian, 48 Chinese, 49 and Pakistani 50 subjects.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…In a study performed among 50 HCC patients from the South Valley of Egypt, the authors revealed that the XRCC1 (rs25487*399Gln) allele was significantly increased with the progression of HCC ( p = 0.007) 47 . Likewise, in another study done among 100 HCC patients recruited from the Capital of Egypt, the authors identified that XRCC1 (rs25487*399Gln) allele revealed a statistically significant with an elevated risk of HCC ( p = 0.004) 13 . Furthermore, other reports confirmed the contribution of the XRCC1 (rs25487*p.Gln399Arg) variant with the elevated risk of HCC like those among Italian, 48 Chinese, 49 and Pakistani 50 subjects.…”
Section: Discussionmentioning
confidence: 93%
“…Besides that, our team recognized two reports that examined the correlation of the XRCC1 (rs25487*p.Gln399Arg) variant with the increased risk of HCC among Egyptian subjects but in the provinces rather than the delta region of Egypt 13,47 . In a study performed among 50 HCC patients from the South Valley of Egypt, the authors revealed that the XRCC1 (rs25487*399Gln) allele was significantly increased with the progression of HCC ( p = 0.007) 47 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations